Market share-prices versus their fundamental values: the case of the New York stock exchange. Issue 50 (27th October 2022) - Spilioti, S. N.
ABSTRACT: The accounting valuation model suggests that the differences between predicted, and market shares-prices are considered as valuation errors while the finance valuation approach proposes that these differences are due to the sentiment of investors. In this paper, we use a new version of the residual income valuation model using American data to calculate the fundamental value of a stock and then examine whether price deviations from their fundamental values are due to macroeconomic or psychological factors. The results show that these differences are explained by important macroeconomic and psychological variables.